A quick journey into the diversity of iron uptake strategies in photosynthetic organisms. (2nd November 2021) - Martín-Barranco, Amanda; Thomine, Sébastien; Vert, Grégory; Zelazny, Enric
ABSTRACT: Iron (Fe) is involved in multiple processes that contribute to the maintenance of the cellular homeostasis of all living beings. In photosynthetic organisms, Fe is notably required for photosynthesis. Although iron is generally abundant in the environment, it is frequently poorly bioavailable. This review focuses on the molecular strategies that photosynthetic organisms have evolved to optimize iron acquisition, using Arabidopsis thaliana, rice ( Oryza sativa ), and some unicellular algae as models. Non-graminaceous plants, including Arabidopsis, take up iron from the soil by an acidification-reduction-transport process (strategy I) requiring specific proteins that were recently shown to associate in a dedicated complex. On the other hand, graminaceous plants, such as rice, use the so-called strategy II to acquire iron, which relies on the uptake of Fe 3+ chelated by phytosiderophores that are secreted by the plant into the rhizosphere. However, apart these main strategies, accessory mechanisms contribute to robust iron uptake in both Arabidopsis and rice. Unicellular algae combine reductive and non-reductive mechanisms for iron uptake and present important specificities compared to land plants. Since the majority of the molecular actors required for iron acquisition in algae are not conserved in land plants, questions arise about the evolution of the Fe uptake processes upon land colonization.